The evil men do [large type] - McMahon, John, 1970- (McMahon, John, 1970- Detective P.T. Marsh, 2020)
"A cop takes on a harrowing new case and confronts old personal demons. A hard-nosed real estate baron is dead, and detectives P.T. Marsh and Remy Morgan learn there's a long list of suspects. Mason Falls, Georgia, may be a small town, but Ennis Fultz had filled it with professional rivals, angry neighbors, and a wronged ex-wife. And when Marsh realizes that this potential murder might be the least of his troubles, he begins to see what happens when ordinary people become capable of evil. As Marsh and Morgan dig into the case, it becomes clear that Fultz's death was not an isolated case of revenge. It may be part of a dark web of crimes connected to an accident that up-ended Marsh's life a couple years earlier--and that now threatens the life of a young child. Marsh veers dangerously off track as his search for clues becomes personal and brings him to a place where a man's good deeds turn out to be more dangerous than his worst crimes"--Provided by publisher.